THE IMPORTANCE OF INTERESTING CONTENT IN THE MARKETING OF A PRODUCT IN THE DIGITAL ERA MARKETING - Syahputri, Kharisma; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (Bina Bangsa International Journal of Business and Management, 2024)
The development of the current digital era has affected the world of marketing. Where each company competes with each other to show who is the best. Where at this time in forming good promotions, they no longer use advertising in general but instead use content marketing. The rise of sales using content was seen during the pandemic. To survive in the midst of this pandemic, business actors must be able to work out how to keep their business running. Starting from focusing on digital marketing through websites that are used as e-commerce, social media, search engines, selling through marketplaces, and forming a reseller team to sell their products. This is the right time for business actors to maximize the marketing process with digital marketing services that will provide many benefits. Doing business online must be able to master digital marketing and social media. With good digital content, it is hoped that it will increase consumer buying interest and expand existing markets, because digital media has a very broad market. To explore the effect of digital marketing content on sales, a descriptive approach is used. The results of the study show that content marketing has a significant influence on customer engagement.